Kinetic basis for the competitive recruitment of TolB by the intrinsically disordered translocation domain of colicin E9 - Papadakos, G; Housden, N; Lilly, K; Kaminska, R; Kleanthous, C (2012)
TolB and Pal are members of the Tol-Pal system that spans the cell envelope of Gram-negative bacteria and contributes to the stability and integrity of the bacterial outer membrane (OM). Lipoylated Pal is tethered to the OM and binds the β-propeller domain of periplasmic TolB, which, as recent evidence suggests, disengages TolB from its interaction with other components of the Tol system in the inner membrane. Antibacterial nuclease colicins such as colicin E9 (ColE9) also bind the β-propeller domain of TolB in order to catalyze their translocation across the bacterial OM. In contrast to Pal, however, colicin binding to TolB promotes its interaction with other components of the Tol system. Here, through a series of pre-steady-state kinetic experiments utilizing fluorescence resonance energy transfer pairs within the individual protein-protein complexes, we establish the kinetic basis for such 'competitive recruitment' by the TolB-binding epitope (TBE) of ColE9. Surprisingly, the 16-residue disordered ColE9 TBE associates more rapidly with TolB than Pal, a folded 13-kDa protein. Moreover, we demonstrate that calcium ions, which bind within the confines of the TolB β-propeller domain tunnel and are known to increase the affinity of the TolB-ColE9 complex, do not exert their influence through long-range electrostatic effects, as had been predicted, but through short-range effects that slow the dissociation rate of ColE9 TBE from its complex with TolB. Our study demonstrates that an intrinsically disordered protein undergoing binding-induced folding can compete effectively with a globular protein for a common target by associating more rapidly than the globular protein. © 2012 Elsevier Ltd. All rights reserved.